2009
DOI: 10.1007/s00701-009-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery dissection as an extremely rare cause of spinal epidural hematoma: case report and review of the literature

Abstract: Dissection of the cervical portion of the vertebral artery with subsequent perivascular bleeding is not well recognized as a possible cause of a spinal epidural hematoma. Even though this entity and the underlying cause may be rare, we suggest a vigilant search for vertebral artery injury in cases of ventrally located cervical and upper thoracic epidural hematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Groen et al [9] suggest that 99 % of bleeds have a venous origin though other authors argue that epidural vein pressure is much greater than intrathecal pressure and could not therefore cause a severe spinal cord compression [2]. In the case presented here, operative findings revealed that an epidural vein bleed did indeed cause severe compression of the spinal cord with resultant symptomatology.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Groen et al [9] suggest that 99 % of bleeds have a venous origin though other authors argue that epidural vein pressure is much greater than intrathecal pressure and could not therefore cause a severe spinal cord compression [2]. In the case presented here, operative findings revealed that an epidural vein bleed did indeed cause severe compression of the spinal cord with resultant symptomatology.…”
Section: Discussionmentioning
confidence: 58%
“…In Duffill's series of four patients treated conservatively [5] it seems safe to treat cases of spinal epidural haematoma in whom recovery has started with observation and steroids, providing this is done in a place with on-site MR facilities and surgical support, should urgent laminectomy be required. Conservative management is an acceptable option for those with none or only mild neurological symptoms and for those rapidly improving on observation [2]. Where there is underlying coagulopathy, treatment with clotting factors has resulted in resolution of the haematoma without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When surgical treatment is adopted, usually laminectomy or hemilaminectomy, it should be performed within 48 hours of the onset of symptoms, inclusively, Raasck et al reported that patients who received operative attention within 12 hours of symptoms had 84% recovery rate compared with patients who were operated 24 hours after the onset of symptoms who had a 47% recovery rate 3 9. The outcome following surgery depends on the patient’s level of disability prior to the intervention and the timing of spinal cord decompression 3 6…”
Section: Discussionmentioning
confidence: 99%
“…Both venous and arterial origins of SSEH are described in the literature 1. Vertebral artery dissection (VAD) as the causative factor for SSEH is exceedingly rare, with only two cases reported in the literature 6 7…”
Section: Introductionmentioning
confidence: 99%